Feeding Management and Extent of Commercialisation among the Smallholder Dairy Farmers in Zimbabwe - Tawedzegwa Musitini; Abbysinia Mushunje; Joseph Muroiwa (Journal of Economics and Behavioral Studies, 2019)
This study assessed the effects of grazing and feeding management on the extent of commercialization among the smallholder dairy farmers in Zimbabwe. Using a sample of 225 smallholder dairy farming households selected randomly across 11 smallholder dairy cooperatives in Zimbabwe, data were analysed using descriptive statistics and the ordinary least squares regression method. The study used milk yield as a proxy for commercialization. Farmers whose cows produced higher yield were considered more commercialized than farmers whose cows produced a lower yield. The results indicated that access to better pastures, better feed types, more area under fodder and more feeding frequency positively impact on milk yield. This result indicates that smallholder farmers with better access to enough, appropriate and consistent feed obtain better milk yield from the dairy cows while the poor quality and quantity of feeds are the primary reasons why most smallholder dairy farmers in developing countries like Zimbabwe continue to produce low/uneconomic milk yields. Since purchased dairy feed concentrates are essential in enhancing milk yield, the study recommends that farmers who can afford these should continue using them and where applicable agro-dealers selling these inputs should be supported to establish selling outlets within the farmers reach. However, given the cost of the commercial dairy feeds visa the economic capacity of smallholder milk producers, the study recommends farmer to consider producing their feed by putting more area under fodder than buying commercial feed.